Ultrastructural Adaptation of the Cardiomyocyte to Chronic Mitral Regurgitation - Corporan, Daniella; Segura, Ana; Padala, Muralidhar (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Mitral regurgitation (MR) imposes a volume overload and elevates wall stress, triggering left ventricle (LV) remodeling. Pronounced LV dilationand a gradual decline in cardiac ejection fraction (EF) is observed. The structural changes in the myocardium that define organ level remodeling remain unknown. Cardiomyocyte elongation and slippage have both been hypothesized, but neither are confirmed, nor are the changes to the cardiomyocyte structure known. Using a rodent model of MR, we used immunohistochemistry and transmission electron microscopy (TEM) to describe ultrastructural remodeling of the cardiomyocyte. Methods: Twenty-four male Sprague-Dawley rats (350-400g) were assigned to two groups: group 1) severe MR (n=18), and group 2) control rats that were healthy, age- and weight-matched (n=6). MR was induced in the beating heart using a 23G ultrasound guided needle to perforate the anterior mitral leaflet, and the rats were followed to 2, 10, and 20wks (n=6/time-point). Echocardiography was performed to quantify MR severity and to measure LV volume and function. Explanted myocardial tissue were examined with TEM and immunohistochemistry. Results: MR induced rapid and significant increase in end diastolic volume (EDV), with a 50% increase by 2wks, compared to control. Rise in end systolic volume (ESV) was more gradual, however, by 20wks, both EDV and ESV in MR rats were increased by 126% compared to control. A significant decline in EF was measured at 10wks of MR. At the ultrastructural level cardiomyocyte elongation and increase in cross-sectional area were observed at 2wks. TEM depicted sarcomere shortening, with loss of Z-line and I-band. Cytoskeletal Desmin was disorganized and localized to the intercalated disc in the rats induced with MR. In MR hearts, the linear registry of the mitochondrial arrangement along the sarcomeres was lost, with mitochondrial fragmentation, aggregation, and cristae irregularities. Discussion: In the setting of chronic MR, LV dilatation occurs by cardiomyocyte elongation, which manifests at the ultrastructural level as distinct alterations to the cardiomyocyte sarcomere, cytoskeleton, and mitochondria. Since the cytoskeleton not only provides tensegrity, but has functional consequences, further investigation into the impact of cytoskeletal remodeling on progressive heart failure or recovery of function upon correcting the valve lesion are needed.